The Effect of Statin Therapy on Mortality in Adult Patients with Liver Cirrhosis: An Evidence-Based Case Report - Raksheeth Agarwal; Wismandari Wisnu (Acta Medica Indonesiana)
Background: Liver cirrhosis causes over one million deaths annually worldwide, but its prognosis varies depending on the presence of complications and decompensating events. Reduction of portal pressure is associated with a reduced risk of mortality in cirrhotic patients. Statin therapy has successfully reduced portal pressure in previous studies, but its effects on overall mortality are unclear. This report aims to determine whether statin therapy significantly affects mortality in patients with liver cirrhosis. Methods: A comprehensive literature search was conducted using five electronic databases: PubMed, Scopus, Embase, Ovid MEDLINE, and Web of Science. Meta-analyses, randomized controlled trials (RCTs), and cohort studies were selected based on pre-set inclusion and exclusion criteria. The quality of selected studies was evaluated using critical appraisal tools developed by the Center for Evidence-Based Medicine. Results: One meta-analysis, one RCT, and one retrospective cohort study were included in this report. The meta-analysis and cohort study were of good quality and reported significantly reduced mortality with statin therapy in cirrhosis patients. However, the RCT had poor validity and did not report a statistically significant difference in mortality between the intervention and control groups. The survival benefits of statins may be limited to Child–Pugh A and B patients only, but this requires confirmation in a larger population of Child–Pugh C patients. Conclusion: Statins potentially reduce mortality in patients with liver cirrhosis, but more evidence is required before they can be widely recommended in clinical practice for this indication.